APLIKASI ATMEGA 128 DENGAN TAMPILAN HUMAN MACHINE INTERFACE UNTUK MENGONTROL LEVEL CAIRAN PADA TANGKI - Hasanuddin, Hasanuddin; Nugraha, Deny Wiria; Joefri, Yuri Yudhaswana (MEKTRIK)
The Development of engine control system continues to be done because it is very important .Control system is done in various ways, especially in industries such as to monitor the liquid level in the tank using a variety of sensors. Manufacture of control systems based on Human Machine Interface can be the right choice for controlling the tool or machine located in basic electronics laboratories of Department of Electrical Engineering Tadulako.This study formulates the problem how to design the look of Human Machine Interface to control water level so it can be applied to the basic process of feedback and control rig 38-100 servo valve to regulate the flow of water by utilizing IC 0808 DAC (Digital to Analog Converter) as a tool to convert digital data into analog and then processed by microcontroller ATmega 128 which will control the servo valve .The method used in this study is a qualitative method based on experiments and the results is displayed by combining between HMI Software and Delphi. Reading of level is done at output current 4-20mA using potentiometer 250 â„¦ and complex circuit. Reading results in analog data wchich is used to Control Servo Valve.